2011
DOI: 10.1007/s10067-011-1909-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal ultrasound and clinical follow-up of Baker’s cysts injection with steroids in knee osteoarthritis

Abstract: This study was conducted to assess ultrasound (US) and clinical changes of Baker's cyst (BC) of patients with knee osteoarthritis (OA) after steroid injection. Patients with knee OA complicated with symptomatic BC (40) were treated with US-guided direct (posterior) aspiration. The injection of 40 mg triamcynolone acetonide was in 20 patients direct into the BC and in other 20 subjects intra-articular (anterior). BC diameters (longitudinal, transverse, and thickness) were measured and followed up with US at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 22 publications
1
36
0
1
Order By: Relevance
“…In patients with arthritis, US is better than physical examination for detecting knee effusion and BCs . Additionally, US‐guided injections and aspirations allow more accurate interventions and quantitative assessment of the treatment response …”
Section: Introductionmentioning
confidence: 99%
“…In patients with arthritis, US is better than physical examination for detecting knee effusion and BCs . Additionally, US‐guided injections and aspirations allow more accurate interventions and quantitative assessment of the treatment response …”
Section: Introductionmentioning
confidence: 99%
“…Most studies evaluated injections into a single structure (42/49 (86%)),17 51 54 69 80 84–87 90–95 97–101 103–113 115–125 but seven studies (14%) investigated injections into more than one structure 52 71 88 89 96 102 114. In decreasing frequency, studies evaluated injections into bursae (19/49 (39%)),17 51 52 54 69 87 91–93 95 97 100 101 103 105 110 115 121 123 tendon sheaths (9/49 (18%)),71 89 102 106 108 111–113 116 tendons or fascia (8/49 {(16%)),96 102 107 112 119 120 124 125 perineural regions (6/49 (12%)),85 88 94 104 109 122 muscles (5/49 (10%)),86 97 114 117 118 cysts (2/49 (4%)),84 90 peritendinous regions (2/49 (4%)),71 102 wounds (1/49 (2%))52 and periarticular spaces (1/49 (2%)) 80…”
Section: Resultsmentioning
confidence: 99%
“…Acebes et al reported successful results following aspiration of cyst contents and KS injection in osteoarthritis related cases [17]. In similar cases, Bandinelli et al also reported successful results using US-guided steroid injection directly into the cyst and intraarticular steroid injection; both methods were considered effective [18]. In the treatment of Baker's cyst accompanied with RA, Hofman-González et al stated that methotrexate application to the cyst may be an alternative method for patients with surgical risk factors [20].…”
Section: Discussionmentioning
confidence: 99%